Armenian atrocities - Toynbee, Arnold, 1889-1975 (My University, 1915)
In 1914 Turkey a Holy War had been proclaimed and the Sultan's Petwa called 300,000,000 Moslems to arms. According to Arnold Toynbee in his 1915 book "Armenian Atrocities," it was during this time an effort at the murder of a nation was made. Toynbee provides evidence of an apparently methodical and organized massacre of a people, carried out with frightful cruelty and callous barbarism at the hands of Turkish authorities
The murder of a nation
By Arnold J. Toynbee ... with a speech delivered by Lord Bryce in the House of Lords. - London ; New York : Hodder & Stoughton, 1915. - 4 p. l., 5-117 p. : 1 ill., double map ; 18 cm.
Տվյալները՝ ինտերնետային կայքից
https://www.pdfdrive.com/armenian-atrocities-the-murder-of-a-nation-e186730769.html
Keywords: Armenian Genocide, 1915-1923; World War, 1914-1918-Armenia-Atrocities